Econometric Estimation of Bilateral Transboundary Trade between Russia and China - Zharicov, Evgenie P.; Kravchenko, Alla A.; Sergeeva, Olesya O.; Stetsyuk, Victor V. (International Journal of Economics and Financial Issues, 2016)
The article focuses on the estimation of bilateral transboundary trade between Russia and China. The authors have suggested a hypothesis about the factors, which influence trade flows between the countries involved in trade relations. The research has resulted in a multiplicative model of the dependence of trade flow intensity upon several factors. Empirical estimation has shown that the coefficients used with the main variables of the model are relevant, thus proving the theoretical significance of the model. In the course of this research, the authors have concluded that the size of countries' economies and their membership in the WTO determine the intensity of trade flows between the countries. Keywords: Transboundary trade, Trade flows, Gravity model, Multiplication model, Trade turnover JEL Classifications: F12, F17